2022
DOI: 10.1029/2022gl101249
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Ice‐Sheet Meltwater Reduces Transient Warming and Climate Sensitivity Through the Sea‐Surface Temperature Pattern Effect

Abstract: Coupled global climate models (GCMs) generally fail to reproduce the observed sea‐surface temperature (SST) trend pattern since the 1980s. The model‐observation discrepancies may arise in part from the lack of realistic Antarctic ice‐sheet meltwater input in GCMs. Here we employ two sets of CESM1‐CAM5 simulations forced by anomalous Antarctic meltwater fluxes over 1980–2013 and through the 21st century. Both show a reduced global warming rate and an SST trend pattern that better resembles observations. The mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…The ocean physics we discuss in the context of OHUE may additionally modulate future climate through a surface warming “pattern effect” (Armour et al., 2013; Gregory & Andrews, 2016; Stevens et al., 2016; Xie, 2020). Recent work highlights how surface warming patterns are disproportionately influenced by heat uptake and warming in the Southern Ocean (Dong et al., 2022; Lin et al., 2021), a region with a strong influence on climate sensitivity (Andrews et al., 2015; Zelinka et al., 2020). However, the link between OHUE and the pattern effect is thus far unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The ocean physics we discuss in the context of OHUE may additionally modulate future climate through a surface warming “pattern effect” (Armour et al., 2013; Gregory & Andrews, 2016; Stevens et al., 2016; Xie, 2020). Recent work highlights how surface warming patterns are disproportionately influenced by heat uptake and warming in the Southern Ocean (Dong et al., 2022; Lin et al., 2021), a region with a strong influence on climate sensitivity (Andrews et al., 2015; Zelinka et al., 2020). However, the link between OHUE and the pattern effect is thus far unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al (2022a) showed that Southern Ocean cooling can cause a two-way teleconnection that results in a similar SST pattern to observed trends. This implies that other sources of Southern ocean cooling, such as increased surface freshening (Pauling et al, 2016;Haumann et al, 2020;Dong et al, 2022b), might also impact global SST trends. Nonetheless, the anomalous circulation associated with LFC1 indicates a strengthening of the circumpolar westerlies and favors strong surface cooling throughout much of the Southern Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of idealized Southern Ocean freshwater hosing simulations published (Dong et al., 2022; Hansen et al., 2016; Li, Marshall, et al., 2023; Pauling et al., 2016; Rye et al., 2020) and efforts are underway to build an understanding of the robustness of these results (Swart et al., 2023). However, due to an understandable desire to find a strong signal, the amounts of freshwater added in these simulations have often been much larger than the estimated observed cumulative anomalous mass flux from the 1990s to the present.…”
Section: Introductionmentioning
confidence: 99%
“…feedbacks (Dong et al, 2022;Kim et al, 2022). One specific forcing that was not included in the CMIP5/6 models is the freshwater from historical changes in the mass balance of the Antarctic ice sheet and surrounding ice shelves (Bintanja et al, 2013).…”
mentioning
confidence: 99%